Pengaruh Kepuasan Kerja dan Komitmen Organisasional terhadap Kinerja Karyawan pada PT. Bank Cimb Niaga Kendari - Rustam Supendy (LP3M Universitas Muhammadiyah Kendari, 2022)
This study aims to determine the effect of job satisfaction and organizational commitment on employee performance at PT. Bank CIMB Niaga Kendari. The research is motivated by the demand to be able to improve the quality of its human resources, so that the company's overall performance can excel in banking competitiveness. This study applies quantitative research procedures by distributing questionnaires to respondents totaling 31 employees. The analytical method used is the method of multiple linear regression analysis. The results of the study concluded: 1) job satisfaction and organizational commitment have a positive and significant effect on employee performance at PT. Bank CIMB Niaga Kendari; 2) job satisfaction has a positive and significant effect on employee performance at PT. Bank CIMB Niaga Kendari; and 3) organizational commitment has a positive and significant effect on employee performance at PT. Bank CIMB Niaga Kendari.